Evaluation of lease accounting under IFRS 16 in comparison with the previous standard : analysis of the new standard’s impact on publicly-listed companies in Turkey - Meteriz, Özen (My University, 2019)
Günümüz ekonomilerinde modern işletmeler tarafından geleneksel yapıdaki işletmelere kıyasla dış finansmana daha sıklıkla başvurulduğu görülmektedir. Bunun bir yansıması olarak işletmeler tarafından kullanımına ihtiyaç duyulan varlıklar satın alınmak yerine kiralama ile edinilmektedir. İşletmeler açısından hem operasyonel yükler hem de finansal yüklerden kurtulma katkısının yanında aşırı sermaye gereksinimini de ortadan kaldırmaktadır. Bu durum geleneksel kiralama muhasebesinin de değişen iş hayatının ekonomik gerçeklerini iyi yansıtmadığı gerekçesiyle yenilenmesine neden olmuştur. Yenilenen kiralama muhasebesi çerçevesinde kiracılar açsından kiralamaların sınıflandırılmasına gerek kalmamakta dolayısıyla tek bir kiralama muhasebesi modeli getirilmiştir. Kiralamanın temelinde finansman sağlanma amacı yer aldığı düşüncesiyle kiralama işlemlerinin kredili varlık alımı şeklinde muhasebeleştirilmesi öngörülmüştür. Yeni kiralama muhasebesi modeli çerçevesinde işletmelerin temel finansal göstergelerinde de önemli değişiklikler gündeme gelmiştir. Bu doğrultuda çalışmamızın amacı halka açık işletmelerin yeni kiralama muhasebesini öngören TFRS 16’yı uygulamaya başlamaları ile finansal göstergelerinde ne ölçüde değişiklikler olduğunun ortaya koyulmasıdır.

In today's economies, it is seen that modern businesses are more frequently applied to external finance compared to traditional companies. As a reflection of this, assets that are required by the companies are acquired by leasing instead of purchasing. In addition to both operational and financial burdens, it eliminates the need for excessive capital. This situation led to the renewal of traditional leasing accounting that it does not reflect the economic realities of the changing business life. Within the framework of new leasing accounting, there is no need to classify leases in terms of lessees and thus a single leasing accounting model has been introduced. It is foreseen that the leasing transactions will be accounted for as the purchase of assets by loan with the idea that the purpose of the lease is to provide financing. Within the framework of the new leasing accounting model, significant changes in the basic financial indicators of the enterprises have also come into the agenda. Accordingly, the purpose of our study is to reveal the extent to which changes in the financial indicators are introduced by the publicly listed companies starting to apply TFRS 16, which provides for new lease accounting.
Keywords: Accounting; Business; IFRS 16; İşletme; Kiralama; Muhasebe; TFRS 16; TFRS 16 Leases; UFRS 16